How can ecology-based civics learning media "PKN Ekologi" foster ecological competence in students? - Feriandi, Yoga Ardian; Ulfah, Risti Aulia (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
This study aims to evaluate the effectiveness of learning media in Citizenship education learning for junior high school students. PKN Ecology is a digital-based learning media that adopts the principle of augmented Reality. This study was conducted using a quasi-experimental method with the control and experimental classes taken from students of SMPN 11 Madiun City, East Java. The number of students used as the research sample is 83, n = 83, consisting of 42 in the experimental and 41 in the control classes. The results showed that the Ecological Civics Media was proven to impact improving ecological competence for middle school students positively. In addition, ecological civics media has been proven to increase student interest in enhancing learning.